Integritas Mahasiswa STIPAK Malang dalam Mengikuti Kuliah Daring - Listio, Siani; Saputra, Hengki (STIPAK Malang, 2023)
Based on the researchers' observations while attending online lectures, the researcher found that some students did not pay attention to the lecturer explaining, take a walk around , playing social media/games, doing other subject assignments , not having permission to turn off the camera, talking/discussing with the people around him when the lecturer explained, he was always late for zoom so the researchers decided to conduct a study entitled